The effect of jujube oil on some biological activities of Culex pipiens mosquito - El Kholy, Samar Ezzat; El Husseiny, Iman Mohamed; Kenawy, Dr.Mohamed Amin; Morsy, Dr.Tosson Aly (JOURNAL OF ADVANCES IN BIOLOGY, 2015)
Synthetic insecticides are quick, effective and most popular methods of pest control. But because of their unfavorable effects on environment and non-target organisms, there is a growing need to find new, safe effective alternatives. Plant extracts represent the most promising alternative. The present study aims to evaluate jujube plant as a promising candidate. LC40 of Jujube oil and Jujube extract using petroleum ether as a solvent were investigated against Culex pipiens larvae. The results showed the reduction of egg hatchability, interruption of molting stages and the inhibition of adult mosquitoes emergence cause by application of LC40 jujube oil and jujube extract at 3rd larval stage. Sex ratio was reduced by jujube extract but pure jujube oil has no effect on sex ratio. In the light of these results, jujube plant is recommended as a promising herbal candidate for integrated pest management instead of chemical insecticides.